Enantioseparation by simulated moving bed chromatography: modeling, simulation and operation - Pais, Luís S. (2010)
The paper deals with chiral separation by Simulated Moving Bed chromatography. A practical tool for choosing the better SMB operating conditions as a function of the feed flow rate is proposed. The operation of a pilot unit of SMB, Licosep 12-26 (Novasep, France), is carried out for the separation of bi-naphthol enantiomers. Experimental results and model predictions are compared in terms of process performance and internal concentration profiles.